2007
DOI: 10.1007/s00167-007-0466-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic fixation of anterior cruciate ligament tibial avulsion fractures using bioabsorbable suture anchors

Abstract: This article describes a new technique for the arthroscopic reduction and fixation of anterior cruciate ligament (ACL) tibial avulsion fractures using bioabsorbable suture anchors. This described technique requires the use of anterolateral, anteromedial, medial mid-patellar, and lateral mid-patellar portals. A suture hook loaded with No. 2 polydioxanone (PDS) was used to pierce the ACL through the anteromedial or anterolateral portal, and bioabsorbable suture anchors were inserted through the medial and latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 21 publications
0
40
0
3
Order By: Relevance
“…In et al 6 described the arthroscopic suture anchor technique with good results. They used 3 or 4 suture anchors to hold the bony fragments at the edge of the ACL avulsion fragment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In et al 6 described the arthroscopic suture anchor technique with good results. They used 3 or 4 suture anchors to hold the bony fragments at the edge of the ACL avulsion fragment.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although screw fixation has strong purchasing power and can be generally applied to a large fracture fragment, the possible disadvantages of screw fixation are the possible breakage of fracture fragment, the impingement of a screw head during knee extension, and the requirement for a secondary procedure for screw removal. 4 In et al 7 studied ACL fixation strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,7,8 Most of the ACL tibial avulsion fractures are just a sliver of bone being held together by the fibres of the ACL. The fracture bed is of poor bone quality due to the fracture.…”
Section: Displaced Acl Tibial Avulsion Fractures (Meyers Andmentioning
confidence: 99%
“…9 There is risk of screws backing out into the joint, posterior neurovascular injury, extension block by the screw head or washer during the postoperative period and need for hardware removal after 8 to 10 weeks. 4,8 Use of single or multiple staples have the same disadvantage as that of screws and they are placed in the fractured bone bed which has poor hold for implants. Sundararajan et al reported backing out of a staple in one out of twenty two patients in their study.…”
Section: Displaced Acl Tibial Avulsion Fractures (Meyers Andmentioning
confidence: 99%